The influence of train noise in residential areas (case study in a residential area near railways in winongo district - Oktaria, Dhina Setyo; Priyanto, Sapto; Budiarto, Balla Wahyu (Trigin Publisher, 2024)
Train transportation is a popular choice for the mobility of Indonesian people, especially in areas with extensive railway networks such as Java. However, the impact of noise produced by trains can pose a serious problem for residents living near train tracks. This research examines the influence of train noise on residential areas in Winongo Village, Madiun City, focusing on comfort factors, health, and noise mitigation efforts. The aim is to determine the effect of noise on residents living around the railway tracks. The research method employed is quantitative, with both primary and secondary data collection. Primary data were obtained through questionnaires distributed to residents living near the railway line. The results of data analysis indicate that the variable related to health, with a Sig value of 0.744, shows that the significance value is greater than 0.05, suggesting that health issues due to train noise may not be significant in the residential area of Winongo Village. The influence of the comfort variable (X1) on the noise variable (Y) is 0.558, indicating a moderate impact, while the influence of noise mitigation efforts (variable X2) on noise is 0.106.00, suggesting a minor impact. Based on these findings, this research can serve as a basis for formulating better policies concerning the influence of train noise in residential areas